Nommer les rues : les traces d’une implication citoyenne à Paris (1871-1898) - Eurydice Boussac (L'Atelier du CRH)
In the aftermath of its proclamation in 1870, the Third Republic, like all the regimes that preceded it since the Revolution, set up street names as a major political issue, to establish its legitimacy and assert its advent over the Empire. In the capital, this prerogative was shared between the Prefect, who represented the State, and the town council of Paris, which was trying to acquire more autonomy. This article moves away from the traditional institutional prism to get closer to the inhabitants, who were the first to be affected by these changes, which shook up their ordinary landmarks and impacted their urban experience. Based on fifty letters from citizens, who wrote to the prefecture or the town council between 1871 and 1898, the article addresses the question of the motives and argumentative strategies adopted by the petitioners, and proposes to understand how this original involvement is indicative of a citizen’s desire to participate and to be fully involved in the making of the city